A rare case of neonatal Apert syndrome (Indian Journal of Case Reports, 2017)
Apert syndrome is a rare Type I acrocephalosyndactyly syndrome. It is a congenital disorder characterized by premature fusion of cranial sutures (craniosynostosis), malformation of skull, hands, face, and feet. Apert syndrome has an incidence of 1/50,000 to 1/80,000 live births. It is classified as a branchial arch syndrome, affecting the first branchial or pharyngeal arch, the precursor of the maxilla and mandible. Disturbances in the development of branchial arches in the fetal development create lasting and widespread effects. It is inherited as an autosomal dominant and occurs due to the gene mutations in the receptors of the fibroblast growth factor. Management of Apert syndrome requires multidisciplinary approach. We, hereby, report a case of a 5?h?old neonate with Apert syndrome.